Salvage Stereotactic Body Radiotherapy for Locally Recurrent Non-Small Cell Lung Cancer after Sublobar Resection and I125 Vicryl Mesh Brachytherapy - Gill, Beant S.; Clump, David A.; Burton, Steven A.; Christie, Neil A.; Schuchert, Matthew J.; Heron, Dwight E. (Frontiers in Oncology, 2015)
Purpose Locally recurrent non-small cell lung cancer (LR-NSCLC) remains challenging to treat, particularly in patients having received prior radiotherapy. Heterogeneous populations and varied treatment intent in existing literature result in significant limitations in evaluating efficacy of lung re-irradiation. In order to better establish the impact of re-irradiation in patients with LR-NSCLC following high-dose radiotherapy, we report outcomes for patients treated with prior sublobar resection and brachytherapy that subsequently underwent stereotactic body radiotherapy (SBRT). Methods A retrospective review of patients initially treated with sublobar resection and I125 vicryl mesh brachytherapy, who later developed LR-NSCLC along the suture line, was performed. Patients received salvage SBRT with curative intent. Dose and fractionation were based on tumor location and size, with a median prescription dose of 48 Gy in 4 fractions (range 20–60 Gy in 1–4 fractions). Results Thirteen consecutive patients were identified with median follow-up of 2.1 years (range 0.7–5.6 years). Two in-field local failures occurred at 7.5 and 11.1 months, resulting in 2-year local control of 83.9% (95% CI, 63.5–100.0%). Two-year disease-free survival and overall survival estimates were 38.5% (95% CI, 0.0–65.0%) and 65.8% (95% CI, 38.2–93.4%). Four patients (31%) remained disease-free at last follow-up. All but one patient who experienced disease recurrence developed isolated or synchronous distant metastases. Only one patient (7.7%) developed grade ≥3 toxicity, consisting of grade 3 esophageal stricture following a centrally located recurrence previously treated with radiofrequency ablation. Conclusion Despite high-local radiation doses delivered to lung parenchyma previously with I125 brachytherapy, re-irradiation with SBRT for LR-NSCLC results in excellent local control with limited morbidity, allowing for potential disease cure in a subset of patients.